2012
DOI: 10.1111/j.1365-2222.2012.04047.x
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptors 2, 3 and 4 and thymic stromal lymphopoietin expression in fatal asthma

Abstract: Background Airway inflammation in asthma involves innate immune responses. Toll-like receptors (TLRs) and thymic stromal lymphopoietin (TSLP) are thought to be involved in airway inflammation, but their expression in asthmatics’ both large and small airways has not been investigated. Objective To analyze the expression of TLR2, TLR3, TLR4 and TSLP in large and small airways of asthmatics and compare their expression in smoking and nonsmoking asthmatics; to investigate whether TLR expression is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 52 publications
2
32
0
1
Order By: Relevance
“…This is relevant to clinical findings that levels of TSLP in airway epithelia and lamina propria are elevated in patients with severe 22 or fatal asthma 27 . TSLP expression can be induced in bronchial epithelial cells in response to various danger signals including protease antigens such as those of the house dust mite 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is relevant to clinical findings that levels of TSLP in airway epithelia and lamina propria are elevated in patients with severe 22 or fatal asthma 27 . TSLP expression can be induced in bronchial epithelial cells in response to various danger signals including protease antigens such as those of the house dust mite 37 .…”
Section: Discussionmentioning
confidence: 99%
“…TSLP is especially relevant to corticosteroid resistance in inflamed airways. Bronchial epithelial cells produce TSLP and the amounts of TSLP in the lung are significantly elevated in the asthmatic airways 22,26,27 . As shown here, the inhibition of TSLP or its key signalling molecule, STAT5, can restore the sensitivity of NH cells to corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of TLR2 was reported to be highly elevated in patients with asthma compared with control subjects (11). In atopic dermatitis, the skin of patients is frequently colonized by SA and other TLR2-activating bacteria, associated with Th2-biased immune activation (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TLR2 participates in the immune response to Mycoplasma pneumonia (7), Chlamydophila pneumonia (8), and Staphylococcus aureus (SA) (9), and it has been shown that these TLR2 ligandexpressing pathogens are associated with acute exacerbations of asthma (10). Expression of TLR2 was shown to be up-regulated in asthmatic epithelial cells and in nasal epithelial cells from patients with chronic rhinosinusitis (CRS) (11)(12)(13).…”
Section: Clinical Relevancementioning
confidence: 99%